The Algerian investment climate between realism and the efficiency of attracting FDI: analytical study - Mabrouk, Bouguerra; Benzaala, Ismail; Belbel, Riad (The journal of contemporary issues in business and government, 2023)
This scientific paper aims to devote scientific and practical interests in addressing foreign direct investment, by highlighting the extent to which changes in the investment climate affect the flows of this type of investment, while addressing the various appropriate measures related to improving the Algerian business climate, and by establishing the various conceptual and theoretical economic literature explaining the variables of the study, and studying and analyzing the various data and data extracted from (UNCTAD), and some other specialized international bodies, which reflect the reality of the Algerian investment climate, and analyze its attractiveness to foreign direct investment. It has been concluded that the various amendments to the attractions adopted by Algerian governments to improve Algeria's investment climate have not yet lived up to the hoped-for levels of FDI inflows, remain insufficient, and require other bold and courageous improvements, such as embodying stability in laws (such as the new investment law), offering more incentives to investors, especially foreigners, freeing investment agencies from excessive administrative domination, and other encouraging factors.